2004
DOI: 10.1115/1.1739409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultra-Thin Liquid Lubricant Films on Dynamics of Nano-Spacing Flying Head Sliders in Hard Disk Drives

Abstract: This paper describes the effect of ultra-thin liquid lubricant films on air bearing dynamics and flyability of nano-spacing flying head sliders in hard disk drives. The dynamics of a slider was monitored using Acoustic Emission (AE) and Laser Doppler Vibrometer (LDV). The disks with lubricant on one half of disk surface thicker than the other half as well as with uniform thickness lubricant were used to investigate the interactions between the slider and lubricant film experimentally. As a result, it was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This may be because the mobility of A20H lubricants is less than Zdol. In fact, the lubricant mobile layer or lubricant mobility suppresses the slider vibration when the slider contacts with the disk [2]. Fig.1.…”
Section: Wtc2005-63622mentioning
confidence: 98%
“…This may be because the mobility of A20H lubricants is less than Zdol. In fact, the lubricant mobile layer or lubricant mobility suppresses the slider vibration when the slider contacts with the disk [2]. Fig.1.…”
Section: Wtc2005-63622mentioning
confidence: 98%
“…Most recently, the effects of an ultrathin liquid lubricant film on air bearing dynamics and flyability in a spacing of less than 10 nm has been studied. As a result, it was found that the flying height at which sliderlubricant contact occurs depends on the mobile lubricant film thickness under the conditions that the total lubricant film thicknesses are the same and the lubricant bonded ratios are different [6]. Thus far, however, research on slider-lubricant interactions for contact sliders has not been carried out, in spite of the above-mentioned investigations.…”
Section: Introductionmentioning
confidence: 96%
“…The magnitude of slider vibration during contact for the Z-DOL was also found to be smaller than the A20H's. It is because Z-DOL lubricant has a higher mobility than A20H lubricant which has better slider vibration suppression during event of any slider-disk contact [18].…”
Section: Intermolecular Force Flying Height Hysteresis and Interfacementioning
confidence: 99%